2017
DOI: 10.1155/2017/9391436
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Year Follow-Up of Laser In Situ Keratomileusis for Moderate to High Myopia

Abstract: Purpose To assess the long-term clinical outcomes of conventional laser in situ keratomileusis (LASIK) for moderate to high myopia. Methods We retrospectively examined sixty-eight eyes of 37 consecutive patients who underwent conventional LASIK for the correction of myopia (−3.00 to −12.75 diopters (D)). At 3 months and 1, 4, 8, and 12 years postoperatively, we assessed the safety, efficacy, predictability, stability, mean keratometry, central corneal thickness, and adverse events. Results The safety and effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 35 publications
1
33
0
2
Order By: Relevance
“…This table reports data before retreats respectively ( Fig. 1f), which is comparable or better than other lower myopia studies [9,16,[23][24][25][26][27][28][29][30][31][32] (Table 3). A better measure of regression effect, than the traditionally reported postoperative SEQ, is the amount of myopic development postoperatively.…”
Section: Complicationssupporting
confidence: 80%
“…This table reports data before retreats respectively ( Fig. 1f), which is comparable or better than other lower myopia studies [9,16,[23][24][25][26][27][28][29][30][31][32] (Table 3). A better measure of regression effect, than the traditionally reported postoperative SEQ, is the amount of myopic development postoperatively.…”
Section: Complicationssupporting
confidence: 80%
“…Serrao S et al [ 16 ] reported the safety index of the high myopia eyes treated by PRK was 0.81 one year postoperatively. Ikeda T et al [ 17 ] found 77% of high myopic eyes showed no change or gain in CDVA one year after LASIK. Torky MA et al [ 14 ] found that 88.2% of high myopic eyes got the SE within±0.50D by SMILE surgery six months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Refractive surgery methods for correcting myopia mainly include corneal refractive surgery and intraocular refractive surgery. For the surgical treatment of patients with moderate to high myopia, corneal refractive surgery, such as excimer laser and femtosecond laser, has certain limitations [4, 5]. Corneal refractive surgery has a large depth of corneal ablation, which changes the biomechanics of the cornea, while intraocular refractive surgery is a phakic posterior chamber intraocular lens (ICL) implantation technique that does not require cutting the cornea, which is relatively safer [6].…”
Section: Introductionmentioning
confidence: 99%